Pembatasan Penggunaan Media Sosial pada Anak dalam Perspektif Jürgen Habermas - Suci Hatika; Rachma Mardana; Fela Syakirania; Viero Varbi Sununianti; Istiqoma Istiqoma; Deni Aries Kurniawan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The development of social media in the digital era has significantly changed children’s social interaction patterns. Besides providing benefits such as easier access to information and opportunities for creativity, social media also brings negative impacts on children’s psychological, social, and moral development. This study aims to analyze the restriction of social media use among children from the perspective of Jürgen Habermas, especially regarding the concepts of the public sphere, communicative rationality, and the colonization of the lifeworld. This research uses a literature study method with a qualitative descriptive approach through the collection and analysis of relevant scientific articles. Data validity was strengthened through inclusion and exclusion criteria as well as source triangulation. The findings indicate that social media use among children has an ambivalent impact. Positive effects can emerge when there is strong parental supervision, while weak supervision increases the risk of exposure to harmful content, psychological problems, and reduced quality of social interaction. Restricting social media use through time regulation, content control, and digital education is considered important for protecting children’s development. From Habermas’s perspective, children are vulnerable in the digital public sphere because of their limited communicative rationality. Therefore, restrictions are viewed as efforts to protect children’s values and rationality from distortion by the digital media system.